2022
DOI: 10.3390/cells11071188
|View full text |Cite
|
Sign up to set email alerts
|

Specific NLRP3 Inflammasome Assembling and Regulation in Neutrophils: Relevance in Inflammatory and Infectious Diseases

Abstract: The NLRP3 inflammasome is a cytosolic multimeric protein platform that leads to the activation of the protease zymogen, caspase-1 (CASP1). Inflammasome activation mediates the proteolytic activation of pro-inflammatory cytokines (IL-1β and IL-18) and program cell death called pyroptosis. The pyroptosis is mediated by the protein executioner Gasdermin D (GSDMD), which forms pores at the plasma membrane to facilitate IL-1β/IL-18 secretion and causes pyroptosis. The NLRP3 inflammasome is activated in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 145 publications
(233 reference statements)
1
18
0
Order By: Relevance
“…Subsequent studies have verified that neutrophils can assemble functional inflammasome platforms initiated by AIM2, 75 NLRC4, 35,75–79 NLRP1, 75 NLRP3, 32,34,51,57,75,80,81 and pyrin/MEFV 75,78 . These are discussed in detail below regarding the differential induction of IL‐1β release versus pyroptosis as downstream responses to inflammasome activation in neutrophils.…”
Section: Inflammasomes and Gasdermins As Critical Regulators Of Pyrop...mentioning
confidence: 91%
“…Subsequent studies have verified that neutrophils can assemble functional inflammasome platforms initiated by AIM2, 75 NLRC4, 35,75–79 NLRP1, 75 NLRP3, 32,34,51,57,75,80,81 and pyrin/MEFV 75,78 . These are discussed in detail below regarding the differential induction of IL‐1β release versus pyroptosis as downstream responses to inflammasome activation in neutrophils.…”
Section: Inflammasomes and Gasdermins As Critical Regulators Of Pyrop...mentioning
confidence: 91%
“…In addition, NETosis allows neutrophils to abundantly release of S100A8/A9 proteins and induce the recruitment of more neutrophils ( 59 ). NETs can activate macrophage NLRP3 to produce IL-1β and IL-18, thus exerting powerful proinflammatory effects, where IL-18 in turn can promote an increase in circulating NETs, creating a vicious cycle that further amplifies inflammation ( 60 , 61 ). Here, notably, patients with common LNK loss-of-function activate oxidized phospholipid (OxPL)-dependent platelet-neutrophil aggregation in vivo , promoting NETosis ( 62 ), and it has been demonstrated that inactivation of OxPL by antibodies after MI in mice protects cardiomyocyte viability and reduces infarct size ( 63 ).…”
Section: Powerful Modulation Of Ventricular Remodeling By Immune Cellsmentioning
confidence: 99%
“…IL-1 can induce the expression of proinflammatory cytokines or chemokines such as IL-6, IL-8, and CCL2 in inflammatory sites. The changes in the expression of these inflammatory cytokines or chemokines recruit monocytes and neutrophils to migrate to infection, injury, and necrosis sites to engulf pathogens, inducing local inflammatory response, and even promoting the activation of dendritic cells and neutrophils; this series of chain reactions triggered by IL-1 will eventually help the host to resist the invasion of pathogens and maintain the homeostasis in the host’s intestine [ 40 , 41 , 42 ]. In addition, Judy Lieberman’s research shows that NLRP3 can affect lamina propria mononuclear cells to secrete more IL-1β.…”
Section: The Relationship Between the Nlrp3 Inflammasome And Intestin...mentioning
confidence: 99%